Coloration study heat-cured polymer materials for denture base - Setiyani, Rezki; Salim, Urip Agus; Mahardika, Muslim; Dharmastiti, Rini; Arifvianto, Budi (Jurnal Teknosains, 2025)
The color of denture base material is important in dentistry to achieve a natural gingival aesthetic. No universal standard for denture base color, due to it difficult for dentists and dental laboratory technicians to achieve consistent results. This study proposes a method for identifying the color of artificial gums made from heated cure polymers with coloring agents. This study also examined the effect adding color agent on the hardness of denture base material and the effect of artificial saliva immersion on coloring. New coloring agents, namely pink (P), red (M), and purple (U), were added to create new colors in this study. Seven specimens from light to dark colors were made. The resulting specimens were photographed and analyzed using Adobe Photoshop software to obtain the L*, a*, and b* values for each specimen, which were then analyzed using the CIELAB formula. The results of the material hardness test showed a significant change between the immersion and non-immersion groups (p-value 0.00<0.05), while the group between 10-day and 20-day immersion showed no significant change (p-value 0.65>0.05). In materials without added color, the hardness value is 85.3 - 86.3 HSD, while in materials with added color, the hardness value increases to 85.5 - 87.7 HSD. The results of the saliva immersion test showed changes in the range of 2.51 - 5.98 for 10 days of immersion and 0.85 - 4.22 for 20 days of immersion. Based on these results, most of the color changes are still below the clinical acceptance threshold of less than 4.1. Therefore, it can be concluded that the color changes that occur after soaking are still clinically acceptable.